(untitled) (Research, Society and Development, 2022)
The aim of this study is to evaluate the periodontal condition of patients treated at the Dental School Clinic of the State University of Paraíba – UEPB (as per its Portuguese acronym), campus I, Campina Grande, Paraíba, investigating its association with the behavioral characteristics and habits of the population studied. This is a cross-sectional, quantitative and analytical study with medical records. It was used as exclusion criteria the incompleteness of data or the absence of signature of the written informed consent form by the patient. The analyzes were performed by SPSS 20.0. To characterize the population, the data frequencies were distributed. To associate the periodontal condition (gingivitis/periodontitis) and the other variables, Pearson’s chi-square test (or Fisher’s exact test when appropriate) was used, with p < 0.05. Of the total 426 records, 42,5% were excluded, remaining 245 records. The frequency of smokers was 10,6% and of ex-smokers 22,0%. Regarding the main complaint, 68,6% sought care for reasons not related to periodontal disease. About the practice of oral hygiene, 121 (49,4%) said they brushed their teeth 3 times a day and 124 (50,6%) said they used dental floss. However, the evaluation of the visible plaque index reflected poor oral hygiene (58,4%). The most prevalent condition was dental calculus (63,7%), predominating in sextant 5 (72,7%). The association between periodontal condition and other variables was statistically significant between periodontitis and smoking (p = 0.003). It is concluded that the report of adequate oral hygiene practice does not reflect the present periodontal condition. It is observed the importance of intensifying orientation actions in oral health.